Comparison of Chain Ladder Method and Cape Cod Method in Reinsurance Incurred But Not Reported (IBNR) Reserve Estimation - Pahlevi, Zievan Ananta; Sudding, Fauziah Nur Fahirah (President University, 2024)
In the era of globalization, there are a lot of risks that surround individuals and companies, including insurance companies. The necessity of risk management becomes important, and risk transfer through reinsurance is crucial in managing the company’s risk profile. As stated in the Otoritas Jasa Keuangan (OJK) Regulations Number 71 of 2016 Article 19 Paragraph (2), reinsurance companies are obliged to establish technical reserves, in which one of the components is Incurred But Not Reported (IBNR) reserve. Considering there is inconsistency from past studies and the importance of accurately calculating IBNR reserves. Therefore, this study aims to compare the results of IBNR reserves using the Chain Ladder method and the Cape Cod method. This study utilizes the Chain Ladder and Cape Cod models that are being applied in Microsoft Excel to calculate the IBNR reserves. The secondary data used in this study is the Paid & Reported Loss Triangle 2013-2022 from Munich Reinsurance’s Financial Results. The result of this study shows that the value of IBNR claim reserves generated using the Chain Ladder gives better accuracy, with a 12.8% relative error compared to the Cape Cod method’s 26.9%. Based on the assumptions made, the Chain Ladder model is suitable for portfolios that are just starting or have sufficient amounts of data. Meanwhile, the Cape Cod model is ideal for portfolios that have been operating for a long period.